ANALISIS POSTUR KERJA OPERATOR PERCETAKAN BATAKO DI TB. SUMBER RIZKI PADANG MENGGUNAKAN METODE RAPID UPPER LIMB ASSESSMENT (RULA) - Wahyuni Amalia; Aris Fiatno (Jurnal Teknik Industri Terintegrasi, 2018)
Brick making activities at TB. Sumber Rizki Padang is still done manually using human power and manual equipment. This work is carried out repeatedly which is known can cause injury or spinal disease if the posture at work is not normal. This study aims to analyze the risk of MSD (Musculoskeletal Disorders) and evaluate the work posture of each element of brick making printing work. Based on the results of the NMB (Nordic Body Map) questionnaire distributed to 30 workers, complaints were most often found in the lumbar area ( 90%), back (86.7%), and upper arm (83.3%). Based on the results of calculations using the RULA (Rapid Upper Limb Assessment) method on 7 work postures, it was found that the working posture of mixing material and the process of inserting material into the mold had the largest RULA scores, which were 6 and 4 respectively, which meant that further changes and checks were needed. Improvements to awkward work postures can be done by repairing equipment and workplaces by adjusting to anthropometry from workers.